Oxidative stress in Physella acuta: An integrative response of exposure to water from two rivers of Atlantic Mexican slope - Sedeño-Díaz, Jacinto Elías; López-López, Eugenia (Frontiers in Physiology, 2022)
Freshwater pollution is a complex mixture of xenobiotics due to the wastewater and the various chemicals applied to agricultural lands that reach water bodies. Xenobiotics can exert damage to the aquatic biota threatening the biodiversity of aquatic ecosystems. The oxidative damage and antioxidant responses have been widely investigated in freshwater organisms, mainly in fish and some invertebrates but in freshwater snails are scarce. This study aimed to assess the oxidative stress exerted by potential toxicity of water from two rivers of the Mexican Atlantic Slope (Tecolutla and Tuxpan rivers) in a freshwater mollusk Physella acuta. Lipid peroxidation level and antioxidant enzymes (Superoxide dismutase, Catalase and Glutathione peroxidase) were measured in P. acuta. The bioassay results are associated with water quality characteristics. Water samples were obtained from three study sites for each river (in two seasons: Northern wind and dry). Twelve water quality variables were analyzed, and an additional water sample was used to perform a static bioassay for 96 h with snails grown in laboratory. After the exposure, lipid peroxidation level and the antioxidant responses of P. acuta were assessed, and the Integrated Biomarker Response (IBR) was computed. The highest lipid peroxidation level occurred in organisms exposed to water during the Northern wind season in both rivers. During this season, in the Tecolutla river, the superoxide dismutase activity was able to counteract the lipid peroxidation process, representing an adaptive response. In contrast, in the Tuxpan river, the superoxide dismutase was unable to counteract that process, stimulating CAT and GPx activities. The IBR showed that the Tecolutla river had higher values in the upper reaches than the Tuxpan river, showing a decreasing downstream gradient in both seasons. In the Tuxpan river, during the Dry season, the IBR score showed an increasing downstream gradient. During the Northern wind season, the IBR was higher in the upper reaches of both rivers, possibly due to the increased materials transported by runoff from the catchment, which includes a complex mixture of xenobiotics affecting the health of the sentinel species and aquatic biota in general. Based on our results, Physella acuta is proposed as sentinel species.